Recognizing Persius - Reckford, Kenneth J., 1933-2021 (Martin classical lectures (Unnumbered)., 2009)
Recognizing Persius is a passionate and in-depth exploration of the libellus--or little book--of six Latin satires left by the Roman satirical writer Persius when he died in AD 62 at the age of twenty-seven. In this comprehensive and reflectively personal book, Kenneth Reckford fleshes out the primary importance of this mysterious and idiosyncratic writer. Reckford emphasizes the dramatic power and excitement of Persius's satires--works that normally would have been recited before a reclining, feasting audience. In highlighting the satires' remarkable honesty, Reckford shows how Persius conver.